An empirical study of organizational culture dimensions impacting employee’s performance in IT industry, Tamilna-du - M, Karthik; Vasumathi, A (International Journal of Engineering and Technology, 2017)
Every company has their own unique culture.Â Organizational cultureÂ is a set of norms, values, beliefs and vision that define how employees and managers intermingle within an organization. Irrespective of whether a preset list of company values present or not, an organization develops its own culture. However, organizations havenâ€™t been paying as much attention to organizational culture until now. A 2015 study by Deloitte University Press found thatÂ 87% of the organizationsÂ surveyed now cite culture and employee engagement as their top challenges. Thus the current study aims at analyzing the impact of cultural dimensions on performance management in IT organizations. Analysis, conclusion and recommendations were drawn out based on the research and findings. The study found a significant association between experience of the respondents and their responses towards often getting reminder and warning to complete their tasks. The study has also found a significance variance between age of the respondents and the practices of Human Resource Department. The study has also found an association between variety of tasks being handled and employeesâ€™ performance.Â